Model Tata Kelola CSR Berbasis Collaborative Governance dan Kearifan Lokal - Higau, Emanuel; B, Jauchar; Nurmiyati, Niken (HK-Publishing, 2025)
Abstract This study aims to analyze a CSR governance model based on local wisdom through a collaborative approach between mining companies and indigenous communities in Kampung Tukul, West Kutai. The approach used is descriptive qualitative, with data obtained through in-depth interviews, participatory observation, and documentation studies. The analysis was conducted using the Collaborative Governance theory. The results show that CSR practices in Kampung Tukul have transformed from symbolic to participatory. Cross-actor collaboration has formed deliberative forums, mapped indigenous territories, and developed CSR programs tailored to local cultural values. This process has enhanced social legitimacy, strengthened community institutions, and minimized conflicts. The implication is that a collaborative CSR model based on local wisdom can serve as a sustainable development strategy in indigenous territories, while also being replicated in similar communities with contextual adaptations. Keywords: Corporate Social Responsibility Governance, Indigenous Communities, Collaboration, Participation Abstrak Penelitian ini bertujuan menganalisis model tata kelola CSR berbasis kearifan lokal melalui pendekatan kolaboratif antara perusahaan tambang dan masyarakat adat di Kampung Tukul, Kutai Barat. Pendekatan yang digunakan adalah kualitatif deskriptif, dengan data diperoleh melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi. Analisis dilakukan menggunakan teori Collaborative Governance (Emerson et al., 2012). Hasil menunjukkan bahwa praktik CSR di Kampung Tukul telah bertransformasi dari simbolik menjadi partisipatif. Kolaborasi lintas aktor membentuk forum deliberatif, pemetaan wilayah adat, dan program CSR yang disesuaikan dengan nilai budaya lokal. Proses ini meningkatkan legitimasi sosial, memperkuat kelembagaan masyarakat, serta meminimalkan konflik. Implikasinya, model CSR kolaboratif berbasis kearifan lokal dapat menjadi strategi pembangunan berkelanjutan di wilayah adat, sekaligus direplikasi di komunitas serupa dengan adaptasi kontekstual. Kata Kunci: Tata Kelola Corporate Social Responsibility, Masyarakat Adat, Kolaborasi, Partisipasi